"We embrace winter here": Celebrating place in winter cities. (27th May 2022) - Stout, Madeleine; Collins, Damian; Evans, Joshua
Abstract : Weather is an elementary and fundamental characteristic of place. In any given place we encounter the materiality of weather, local meanings attached to weather, and practices adopted in response to living with weather. Winter cities are places defined by their weather—long, cold winters that can pose challenges to urban life. Efforts to address these challenges centre on place‐making activities, such as seasonal festivals, which seek to enrich public spaces. In this paper, we examine the relationship between winter, place, and placemaking in three Canadian prairie cities. Participants sought to promote a celebratory relationship with winter by changing public attitudes, fostering unique winter experiences, and incorporating winter into their cities' identities. This shift was encouraged by strategies and events that were "authentic" to local context and community. They did not simply reframe winter weather as positive, but recognized the season as presenting both challenges and opportunities. Enabling residents to realize opportunities is critical to being a successful winter city, and requires negotiating a set of dyads: warm/cold, indoor/outdoor, and light/dark. This paper highlights the constitutive role of weather in shaping place, while revealing the agentic ways in which communities act towards and with weather . Key Messages: Weather in winter cities presents challenges for urban life, but also opportunities for celebration and community building. Winter city planners and programmers navigate fundamental tensions in order to foster conditions for celebrating winter. Winter festivals are placemaking activities that seek to tell authentic stories about weather, place, and culture. Embrassons l'hiver : célébrer le lieu dans les villes d'hiver: La météo est une caractéristique élémentaire et fondamentale d'un lieu. Dans tout endroit donné, nous rencontrons sa matérialité, ses significations et les pratiques adoptées pour vivre avec la météo. Dans ce contexte, les villes d'hiver sont des lieux définis par leur climat, c'est‐à‐dire de longues périodes de froids qui peuvent poser des défis à la vie urbaine. Les efforts visant à relever ces défis se concentrent sur des événements locaux, comme les festivals saisonniers, qui cherchent à enrichir les espaces publics au cours de l'hiver. Dans cet article, nous examinons la relation entre l'hiver, le sens du lieu et la création d'événement dans trois villes des Prairies canadiennes. Les participants ont cherché à promouvoir l'idée d'une célébration de l'hiver en changeant les attitudes du public, en favorisant des expériences hivernales uniques et en incorporant l'hiver dans l'identité de leurs villes. Des stratégies et événements considérés comme « authentiques », par rapport au contexte local et à la communauté, ont encouragé ce changement. Ils n'ont pas simplement reformulé le cadre hivernal comme étant positif, ils ont reconnu que cette saison présentait à la fois des défis et des possibilités. Pour être une ville d'hiver réussie, il est essentiel de permettre aux résidents de saisir les opportunités qui s'offrent à eux, ce qui oblige à composer avec diverses dualités : chaud/froid, intérieur/extérieur et lumière/obscurité. Ce texte fait ressortir le rôle constitutif de la météo dans le façonnement du lieu, tout en révélant des modes novateurs de construction sociale de la représentation de l'hiver par les communautés locales .